KEPEMIMPINAN PEREMPUAN DALAM ISLAM - Muhajir (Hukum Keluarga Islam IAIN LANGSA, 2018)
This paper is a simple and concise study conducted in Langsa City, especially in severalsub-districts. To parse this paper well, the author gives the title: